Potensi Fenolik dan Flavonoid Pada Ekstrak Kulit Edamame sebagai Antioksidan untuk Formulasi Lotion - Dinar Andreas Kustiadi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Phenolics and flavonoids are antioxidant compounds found in edamame shells. Phenolics and flavonoids have health benefits including warding off exposure to free radicals, anti-inflammatory, antimicrobial, and can also prevent cancer. This research aims to identify the content of antioxidant compounds in the form of phenolics and flavonoids in edamame shells extract which is used for lotion use using the Uv-Vis spectrophotometer method. The extraction process is carried out by using a mixture of ethanol solvents for analysis (1:10) with variations of 3%, 5%, and 10% extracts. The content of phenolic compounds was analyzed with a wavelength of 730 nm and flavonoids with a wavelength of 409 nm using a Uv-Vis spectrophotometer. Research results show that total phenolic levels are higher than total flavonoid levels. The highest total phenolic level at 10% concentration is 1.7 mg/g while the highest total flavonoid level at 10% concentration is 0.6 mg/g. The antioxidant result in the three variations of the highest sample concentration is at a concentration of 3% which is 50% inhibition. This concentration is due to increased turbidity at higher extract concentrations that have the potential to cause light scattering and increase the measured absorbance value. This study concluded that edamame shells has natural antioxidant potential at 3% concentration variation. This research also provides the potential for the development of phenolic antioxidant compounds and flavonoids as ingredients in the food, pharmaceutical, and cosmetic industries.
Finalisasi Rudy K
Keywords: edamame shells; flavonoids; phenolics; Uv-Vis spectrophotometer.